2021
DOI: 10.1177/20416695211009928
|View full text |Cite
|
Sign up to set email alerts
|

Serum C-Reactive Protein Is Negatively Associated With Olfactory Identification Ability in Older Adults

Abstract: Importance Olfactory deficits are common in aging and associated with several conditions linked to inflammation. A few studies suggest that increased concentration of pro-inflammatory biomarkers may be related to olfactory deficits, but these associations are understudied in population-based samples. Objective To investigate the association between serum concentrations of C-reactive protein (CRP) and olfactory identification level as well as rate of change in aging. Methods We included 1,721 participants (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Based on the prior literature, we considered sociodemographic (age, sex, race, study site, and education), behavioral (smoking, alcohol consumption, and physical activity), vascular and/or metabolic (body mass index (BMI), serum total cholesterol, diabetes, hypertension status, coronary heart disease, and myocardial infarction), genetic (apolipoprotein E gene epsilon 4 allele ( APOE ε 4)), inflammatory (C-reactive protein), blood hemoglobin, and nutritional factor (serum vitamin B 12 ) as the potential risk factors of olfaction [ 17 , 18 , 19 , 20 , 21 , 22 ]. With the exception of sex, race, study site, and education, which were obtained from the visit 1 exam, other risk factors data were obtained from the visit 5 exam.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the prior literature, we considered sociodemographic (age, sex, race, study site, and education), behavioral (smoking, alcohol consumption, and physical activity), vascular and/or metabolic (body mass index (BMI), serum total cholesterol, diabetes, hypertension status, coronary heart disease, and myocardial infarction), genetic (apolipoprotein E gene epsilon 4 allele ( APOE ε 4)), inflammatory (C-reactive protein), blood hemoglobin, and nutritional factor (serum vitamin B 12 ) as the potential risk factors of olfaction [ 17 , 18 , 19 , 20 , 21 , 22 ]. With the exception of sex, race, study site, and education, which were obtained from the visit 1 exam, other risk factors data were obtained from the visit 5 exam.…”
Section: Methodsmentioning
confidence: 99%
“…In older adults, the prevalence of olfactory impairment increases with age and is about two times as high in men as in women and similarly elevated in Black and White individuals [ 2 , 11 , 13 , 14 ]. Studies have also linked smoking [ 2 , 15 ], cardiovascular factors [ 16 , 17 ], diabetes [ 17 ], lower physical activity [ 18 ], and systemic inflammatory markers [ 19 ] with poor olfaction, but findings have been sparse and inconsistent [ 13 , 20 , 21 , 22 , 23 ]. Furthermore, the existing evidence on determinants of olfactory impairment mostly comes from cross-sectional studies [ 13 , 23 , 24 , 25 , 26 ], and only a few prospective studies have investigated the factors associated with longitudinal changes in olfactory function [ 17 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the differential proteins identified, several proteins have been reported to be associated with olfaction.Ekström I et al [14] in 2021 showed that serum C-reactive protein (CRP) levels were negatively correlated with olfactory recognition in aging. And Proft F et al [15] found that diminished sense of smell in patients with granulomatous polyangiitis (GPA) was significantly associated with elevated CRP values.…”
Section: Urine Proteome Changes In Rats Before-after Smelling Sesame Oilmentioning
confidence: 99%